A Novel Approach to Reinstating Tolerance in Experimental Autoimmune Myasthenia Gravis Using a Targeted Fusion Protein, mCTA1–T146 - Consonni, Alessandra; Sharma, Sapna; Schön, Karin; Lebrero-Fernández, Cristina; Rinaldi, Elena; Lycke, Nils Yngve; Baggi, Fulvio (Frontiers in Immunology, 2017)
Re-instating tissue-specific tolerance has attracted much attention as a means to treat autoimmune diseases. However, despite promising results in rodent models of autoimmune diseases no established tolerogenic therapy is clinically available yet. In the experimental autoimmune myasthenia gravis (EAMG) model several protocols have been reported that induce tolerance against the prime disease-associated antigen, the acetylcholine receptor (AChR) at the neuromuscular junction. Using the whole AChR, the extracellular part or peptides derived from the receptor, investigators have reported variable success with their treatments, though, usually relatively large amounts of antigen has been required. Hence, there is a need for better formulations and strategies to improve on the efficacy of the tolerance-inducing therapies. Here, we report on a novel targeted fusion protein carrying the immunodominant peptide from AChR, mCTA1-T146, which given intranasally in repeated μg doses strongly suppressed induction as well as ongoing EAMG disease in mice. The results corroborate our previous findings, using the same fusion protein approach, in the collagen-induced arthritis model showing dramatic suppressive effects on Th1 and Th17 autoaggressive CD4 T cells and up-regulated regulatory T cell activities with enhanced IL10 production. A suppressive gene signature with upregulated expression of mRNA for TGFβ, IL10, IL27 and Foxp3 was clearly detectable in lymph node and spleen following intranasally treatment with mCTA1-T146 compared to untreated animals. EAMG amelioration was accompanied with reduced loss of muscle AChR and lower levels of anti-AChR serum antibodies. We believe this targeted highly effective fusion protein mCTA1-T146 is a promising candidate for clinical evaluation in MG patients.